Effect of lipase hydrolysis on the antibacterial activity of coconut oil, palm mesocarp oil and selected seed oils against several pathogenic bacteria - Lee, Soon Thing; Ariffin, Abdul Azis; Radu, Son; Mohd Ghazali, Hasanah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
The antibacterial activity of solvent-extracted oil of noni (Morinda citrifolia L.), spinach (Spinacia oleracea L.), lady’s finger (Abelmoschus esculentus (L.) Moench), bitter gourd (Momordica charantia Linn.), and mustard (Brassica nigra L.) seed oils, and coconut (Cocos nucifera L.) oil, palm (Elaeis guineensis L.) mesocarp in hydrolyzed and unhydrolyzed form were determined in order to explore their potential usage as antibacterial agent. The hydrolysis process that was catalyzed by immobilized lipase of Rhizomucor miehei (RMIM) showed highest hydrolytic activity with 1.0 ml of added water volume except bitter gourd seed oil and palm mesocarp oil which has maximum hydrolytic activity with added water volume of 5 ml and 2.5 ml respectively. Before hydrolysis, all oil samples did not show inhibition ring zones (IRZ) on any of the tested bacteria strains (Salmonella typhimurium, Listeria monocytogenes and Escherichia coli O157:H7). Hydrolyzed lady’s finger and bitter gourd seed oil showed IRZ on all tested bacteria strains; hydrolyzed mustard seed oil on S. typhimurium and L. monocytogenes; hydrolyzed spinach seed oil and coconut oil on L. monocytogenes; hydrolyzed noni seed oil and palm mesocarp oil did not exhibit IRZ on any of the tested bacteria strains. Most of the hydrolyzed oil exhibit an inhibition activity that was different from their respective dominant fatty acids except noni seed oil and palm mesocarp oil.